Verbos copulativos com locativos em Português Europeu e em Língua Gestual Portuguesa - Morgado, Celda (2020)
Verbs and their syntactic and semantic properties have been studied in several languages, in different theoretical frameworks. However, as for copulative verbs, studies of Sign Languages are still scarce, mainly of Portuguese Sign Language. Therefore, in this paper, some properties of predicative phrases with adjectives, participles and locatives in European Portuguese and Portuguese Sign Language are studied, comparing them with other Oral Languages, in particular Iberian Romance languages, and also with other Sign Languages. Portuguese Sign Language data seem to indicate that the copulative verb is lexically realized when there is a locative predicate and that with a non-locative predicate a null copula occurs.